Emergency contraceptive use in Addis Ababa, Ethiopia: Challenging common assumptions about young people's contraceptive practices. Issue 45 (May 2015) - Both, Rosalijn
Abstract Drawing on an ethnographic case study of young people's (aged 18-29) use of emergency contraceptives (ECs) in Addis Ababa, Ethiopia, this article highlights areas of disconnect between how reproductive health experts envision EC use and local meanings ascribed to ECs by young people. ECs – designed by reproductive health experts to be used only in case of emergency – were preferred by study participants over other contraceptive methods because of their ease of use, discreetness, perceived minimal side effects on beauty and future fertility, and usefulness in navigating reproductive intentions. The findings point to features that young people find desirable when it comes to contraceptive methods and suggest that common assumptions of reproductive health experts about young people's contraceptive practices need to be reconsidered, namely: 1) that young people can plan for prevention of unwanted pregnancy by buying a contraceptive method in advance; 2) that existing contraceptive technologies are appropriate for young people; 3) that young people prefer to use modern contraceptive methods; and 4) that young people in premarital relationships aim to prevent unplanned pregnancy.